Radiation-resistant bacteria in desiccated soil and their potentiality in applied sciences - Khan, Asaf; Liu, Guangxiu; Zhang, Gaosen; Li, Xiangkai (Frontiers in Microbiology, 2024)
A rich diversity of radiation-resistant (Rr) and desiccation-resistant (Dr) bacteria has been found in arid habitats of the world. Evidence from scientific research has linked their origin to reactive oxygen species (ROS) intermediates. Rr and Dr bacteria of arid regions have the potential to regulate imbalance radicals and evade a higher dose of radiation and oxidation than bacterial species of non-arid regions. Photochemical-activated ROS in Rr-bacteria is run through photo-induction of electron transfer. A hypothetical model of the biogeochemical cycle based on solar radiation and desiccation. These selective stresses generate oxidative radicals for a short span with strong reactivity and toxic effects. Desert-inhibiting Rr-bacteria efficiently evade ROS toxicity with an evolved antioxidant system and other defensive pathways. The imbalanced radicals in physiological disorders, cancer, and lung diseases could possibly be neutralized by a self-sustaining evolved Rrbacteria anti-oxidant system. The evolved antioxidant system's direct link with intermediate ROS and indirect influence of radiation and desiccation provide useful insight into richness, ecological diversity, and origin of Rr bacteria capabilities. These distinguishing features of Rr bacteria inhibiting in Deserts are gaining scientific interest. It is a fertile research area with potentiality in the pharmaceutical industry, genetic engineering, biological therapy, biological transformation, bioremediation, industrial biotechnology, and astrobiology.